2016
DOI: 10.1021/acs.energyfuels.6b01478
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of a Non-premixed Organic Dust Flame in a Counterflow Configuration

Abstract: In the present article, an analytical approach is employed to study the counterflow non-premixed dust flame structure in air. Lycopodium is assumed to be the organic fuel in this paper. First, it is presumed that the fuel particles vaporize in a thin zone to form a gaseous fuel to react with the oxidizer. The reaction rate is presumed to be of the Arrhenius type in first order, with respect to the oxidizer and fuel. Mass conservation equations of dust particles, oxidizer, gaseous fuel and the energy conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…For unit fuel Lewis number, enhancement of the oxidizer Lewis number resulted in a reduced a a 0 ratio. These findings are well in line with the reports of Bidabadi et al 18 and Seshadri and Trevino. 41…”
Section: Validationsupporting
confidence: 93%
See 1 more Smart Citation
“…For unit fuel Lewis number, enhancement of the oxidizer Lewis number resulted in a reduced a a 0 ratio. These findings are well in line with the reports of Bidabadi et al 18 and Seshadri and Trevino. 41…”
Section: Validationsupporting
confidence: 93%
“…16 Wilson and Lyons 17 empirically examined a biogas-fueled combustor to study the turbulence in nonpremixed flames with coflow configuration. Bidabadi et al 18 mathematically modeled a nonpremixed organic dust flame inside a counterflow arrangement to illustrate the variations in flame temperature, gaseous fuel, and oxidizer mass fractions with respect to fuel and oxidizer Lewis numbers. In another research study, Bidabadi et al 19 suggested an analytical model to simulate the volatile organic particles-fueled counterflow diffusion flames taking drying and vaporization zones into account.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction process occurs within a very thin zone as the value of Zeldovich number is considered to be very large. The one-stage Arrhenius model is used to describe the reaction process as [32]…”
Section: Mathematical Modeling Of the Reaction And Melting Processesmentioning
confidence: 99%
“…Also, −∞ represents the initial mass fraction of the particles at = −∞. Following correlation is used to define the Lewis number [32] = (15) where and represent the thermal diffusivity and mass diffusivity of fuel or oxidizer, respectively.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation